Mixed Ligand Complexes of Hg-tetrazole-thiolate with phosphine, Synthesis and spectroscopic studies. - Osama'a A. Y. Al-Samrai; Ahmed S. M. Al-Janabi; Eman A. Othman (Tikrit Journal of Pure Science, 2019)
Seven new complexes [Hg(k1-ptt)2](1), [Hg(k1-ptt)2(dppm)](2), [Hg(k1-ptt)2(dppe)](3), [Hg(k1-ptt)2(dppp)](4), [Hg(k1-ptt)2(dppb)](5), [Hg(k1-ptt)2(dppf)] (6), and [Hg(k1-ptt)2(PPh3)2] (7) have been synthesized and characterized. The reaction of two moles equivalent of 1-Phenyl-1H-tetrazole-5-thiol (Hptt) with one mole equivalent of  Hg(oAc)2.xH2O in ethanol solution afford [Hg(k1-ptt)2] (1). Treatment of (1) with one mole equivalent of diphos (diphos : dppm, dppe, dppp, dppb, dppf) or two moles equivalent of PPh3 afforded a complexes of the types [Hg(k1-ptt)2(diphos)] (2-6) or [Hg(k1-ptt)2(PPh3)2] (7). The prepared complexes have been characterized by CHNS elemental analyses, molar conductivity, IR and NMR (1H, 13C and 31P) spectroscopy. In all complexes, the ptt- ligand is bonded through the sulfur atom of deprotonated thiol group, whereas the diphosphine ligands bonded as bidentate chelating and PPh3 bonded as a monodentate, to afford a tetrahedral geometry around the Hg+2 ion.